2002
DOI: 10.1074/jbc.m210526200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-1 Increases Skeletal Muscle Dihydropyridine Receptor α1S Transcriptional Activity by Acting on the cAMP-response Element-binding Protein Element of the Promoter Region

Abstract: Previous work from our laboratory has shown that insulin-like growth factor 1 (IGF-1) increases the expression of the skeletal muscle dihydropyridine receptor (DHPR) ␣ 1 subunit by regulating DHPR ␣ 1S nuclear transcription. In this study, we investigated the mechanism by which IGF-1 enhances expression of the DHPR ␣ 1S gene. To this end, the promoter region of the mouse DHPR ␣ 1S gene was recently cloned and sequenced and various promoter deletion-luciferase reporter constructs were used. These constructs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 42 publications
1
29
0
1
Order By: Relevance
“…2G,H), indicating that TnT3 binds to each independently. TnT3 binding to the Cacna1s promoter region is consistent with our previous report that most transcription factor binding sites are located within 1 kb upstream of the Cacna1s' transcription start site (Zheng et al ., 2002b). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2G,H), indicating that TnT3 binds to each independently. TnT3 binding to the Cacna1s promoter region is consistent with our previous report that most transcription factor binding sites are located within 1 kb upstream of the Cacna1s' transcription start site (Zheng et al ., 2002b). …”
Section: Resultsmentioning
confidence: 99%
“…Our studies indicate that TnT3‐mediated Cacna1 transcription is a primary but not the only mechanism regulation Cav1.1 expression (Zheng et al ., 2002b). Restoring nuclear levels of FL‐TnT3 by calpain inhibition significantly recovers Cav1.1 expression but we do not know how completely.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, research is therefore examining roles of IGF-1 replacement or replenishment as potential treatment for age-related disease and degeneration (Groban, et al, 2006,Schmidmaier, et al, 2006,Sonntag, et al, 2005. We and others have previously shown that IGF-1 overexpression in skeletal muscle of aging mice prevents deleterious effects of age on skeletal muscle and the neuromuscular system as a whole (Barton-Davis, et al, 1998,Gonzalez, et al, 2003,Musaro, et al, 2001,Renganathan, et al, 1998,Zheng, et al, 2002. Since gene therapy is possibly far off in the future, transgenic humans are not feasible at this time.…”
Section: Discussionmentioning
confidence: 99%
“…A major contributor to specific force decline in aging muscle is the decrease in DHPRα1 subunit expression (Delbono, et al, 1995,Gonzalez, et al, 2000,Gonzalez, et al, 2003,Wang, et al, 2000; and IGF-1 overexpression exclusively in skeletal muscle prevents both DHPRα1 subunit and specific force decline (Gonzalez, et al, 2003,Renganathan, et al, 1998,Wang, et al, 1999,Zheng, et al, 2002. We have recently reported that IGF-1 targeted to motor neurons with hIGF-1-TTC injections increased specific force of single intact EDL fibers from aged mice (Payne, et al, 2006).…”
Section: Igf-1 Targeted To Motor Neurons Increases Dhprα1 Subunit Promentioning
confidence: 99%
See 1 more Smart Citation